Can ventral pattern be used for individual recognition of the vulnerable Pyrenean brook newt (Calotriton asper)?. Issue 2 (2021) - Dalibard, Manon; Laffaille, Pascal; Buisson, Laëtitia; Calvez, Olivier; Nguyen-Hong, Morgan; Trochet, Audrey
No abstract available